A socio-psychological portrait of a pathological gambler as a prerequisite for preventing gambling addiction (gambling disorder) - Toporetska, Z.M.; Aymedov , C.V.; Synitska, T.V.; Oliinyk , O.P. (Medicni Perspektivi, 2024)
Gambling always carries risks for the player's mental health, as it can provoke the development of gaming addiction. A direct connection between the socio-psychological portrait of the player, his gaming behavior, and the risks of game addiction can be traced. The purpose of the work is to form a socio-psychological portrait of a "pathological" gambler. The work was performed based on the State Institution "Institute of Forensic Psychiatry of the Ministry of Health of Ukraine". Methods used: CAWI (Computer Assisted Web Interviewing) questionnaires in online gambling establishments; CAPI (Computer Assisted Personal Interviews - server event tracking method) in land-based casinos (more than 9,000 people were interviewed); statistical (for selection and analysis of materials). A questionnaire specially developed by the authors with a point evaluation of the results (from 71 to 90 points) allows us to conclude that the interviewee is a pathological gambler. For the first time in Ukraine, the survey was conducted exclusively among gamblers at gambling establishments. The obtained results made it possible to form a statistically reliable р<0.05 socio-psychological portrait of a pathological gambler, mostly men (87.7%) aged 25-35 years (52.4%) with secondary special (43.4%) or higher education (37.7%). In this group, 94% of people declared their inability to resist the desire to play, and 83.0% thought about stealing money to continue. Of pathological gamblers, 85.0% consider gaming as a means of earning money. All interviewed pathological gamers have experienced continuous gaming for more than 5 hours; 79.2% play almost every day. Such players in 95.0% noticed that they lost more money or spent more time than they planned, 96.0% felt culpable for the game, and 95.0% started the day with a game. Based on this portrait, the authors derived quantitative criteria that the organizer of gambling games can use to prevent gambling addiction among players within the framework of the application of the principles of responsible gaming.